High-Throughput B Cell Epitope Determination by Next-Generation Sequencing - Walker, Lauren M.; Shiakolas, Andrea R.; Venkat, Rohit; Liu, Zhaojing Ariel; Wall, Steven; Raju, Nagarajan; Pilewski, Kelsey A.; Setliff, Ian; Murji, Amyn A.; Gillespie, Rebecca; Makoah, Nigel A.; Kanekiyo, Masaru; et al. (Frontiers in Immunology, 2022)
Development of novel technologies for the discovery of human monoclonal antibodies has proven invaluable in the fight against infectious diseases. Among the diverse antibody repertoires elicited by infection or vaccination, often only rare antibodies targeting specific epitopes of interest are of potential therapeutic value. Current antibody discovery efforts are capable of identifying B cells specific for a given antigen; however, epitope specificity information is usually only obtained after subsequent monoclonal antibody production and characterization. Here we describe LIBRA-seq with epitope mapping, a next-generation sequencing technology that enables residue-level epitope determination for thousands of single B cells simultaneously. By utilizing an antigen panel of point mutants within the HIV-1 Env glycoprotein, we identified and confirmed antibodies targeting multiple sites of vulnerability on Env, including the CD4-binding site and the V3-glycan site. LIBRA-seq with epitope mapping is an efficient tool for high-throughput identification of antibodies against epitopes of interest on a given antigen target.